Pengaruh Current Ratio (CR) Dan Debt To Equity Ratio (DER) Terhadap Return On Assets (ROA) Pada Perusahaan Properti di BEI Periode 2021-2024 - Rafli Maulana Yusuf; Alfiana Alfiana; Siti Kodariah (INDO PUBLISHING, 2026)
The property and real estate sector faced complex challenges in the 2021-2024 period due to post-pandemic recovery and global economic fluctuations. This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) in property companies listed on the Indonesia Stock Exchange (IDX). The research method used is quantitative with a purposive sampling technique, resulting in 10 sample companies with a total of 40 observations during the 2021-2024 period. Data analysis was performed using panel data regression with the selected Random Effect Model (REM). The partial test results (t-test) show that the Current Ratio has no significant effect on ROA with a negative direction. Conversely, the Debt to Equity Ratio has a positive and significant effect on ROA, indicating the effectiveness of using financial leverage in increasing profits. Simultaneously (F-test), CR and DER have a significant effect on ROA. The Adjusted R-squared value of 11.58% shows the contribution of the independent variables in the model, while the rest is influenced by other factors outside the study.